Unusual framework stabilization of Cu(II) and Cu(I) ions in a novel copper-substituted aluminophosphate with AEN topology prepared by one pot synthesis - Gabelica, Z. (2012)
A novel copper-substituted aluminophosphate (CuIST-2) has been synthesized using methylamine as a templating agent. X-Ray diffraction studies provide evidence for an AEN topology similar to the parent Cu-free IST-2.